2020
DOI: 10.3390/ijms21145047
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyopathies and Adrenal Diseases

Abstract: Cardiomyopathies are myocardial disorders in which heart muscle is structurally and/or functionally abnormal. Previously, structural cardiomyocyte disorders due to adrenal diseases, such as hyperaldosteronism, hypercortisolism, and hypercatecholaminism, were misunderstood, and endomyocardial biopsy (EMB) was not performed because was considered dangerous and too invasive. Recent data confirm that, if performed in experienced centers, EMB is a safe technique and gives precious information about physiopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…The direct effects of prolonged hypercortisolism on the myocardium are poorly understood [ 40 , 49 ]. Myocardial biopsies from patients with CS indicate myocardial hypertrophy, fibrosis, and myofibrillolysis [ 50 ]. The increased expression of atrogin-1, a marker of muscle atrophy, was observed [ 51 , 52 ].…”
Section: Cushing’s Syndrome-associated Myopathy: Epidemiologymentioning
confidence: 99%
“…The direct effects of prolonged hypercortisolism on the myocardium are poorly understood [ 40 , 49 ]. Myocardial biopsies from patients with CS indicate myocardial hypertrophy, fibrosis, and myofibrillolysis [ 50 ]. The increased expression of atrogin-1, a marker of muscle atrophy, was observed [ 51 , 52 ].…”
Section: Cushing’s Syndrome-associated Myopathy: Epidemiologymentioning
confidence: 99%
“…In addition to the development of moderate–severe hypertension and RH, PA is associated with important target organ damage and the development of several complications related to pressure overload and to pleiotropic effects of aldosterone on the CV system; moreover, PA is characterized by several metabolic changes, such as metabolic syndrome ( 40 ), cardiac fibrosis ( 48 ), myocardial hypertrophy ( 4 , 49 ), arrhythmias, HF, and deleterious effects on vascular remodeling, such as endothelial dysfunction, and oxidative stress, perivascular inflammatory lesions, fibrosis, platelets activation, and renal function ( 3 , 5 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Primary aldosteronism is characterized by several metabolic changes, such as metabolic syndrome ( 3 ), myocardial hypertrophy and fibrosis ( 4 ), atrial fibrillation ( 5 ), and in particular, heart failure (HF) and deleterious effects on vascular remodeling secondary to endothelial dysfunction ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ang II can induce ET-1 by ROS and ERK ( 78 , 117 ), and ET-1 can not only contract blood vessels but also induce fibroblasts to produce ECM ( 118 ). Ang II can induce aldosterone production in the adrenal cortex, and aldosterone can induce cardiomyocyte apoptosis and cardiomyocyte hypertrophy by activating oxidative stress and regulating ion channels ( 119 , 120 ). Related research has shown that Ang II can increase the secretion of TNF-α and IL-6 ( 121 ), and the mechanism of their participation in VR was described in the following paragraphs.…”
Section: Molecular Pathways Involved In Cardiac Remodelingmentioning
confidence: 99%